2020
DOI: 10.22161/jhed.2.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Competence of Secondary School Students of Bhutan

Abstract: This study on communicative competence of secondary school students of Bhutan was conducted with the lower, middle and higher secondary school students under four districts Chukha, Samtse, Paro and Thimphu. The study aimed to explore why communicative proficiency was generally perceived low as reported by LaPrarie (2014). Random sampling survey questionnaire was administered to 864 students and purposive sampling interviews conducted with 24 teacher and 2 curriculum developers from Royal Education Council. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 2 publications
(3 reference statements)
1
11
0
Order By: Relevance
“…They are observed to be on social media during their leisure time rather than engaging in reading for pleasure. Most of the students lack good communication skills and Choeda et al (2020) found that poor reading habits are a barrier to good communication skills. These behaviors of students towards reading for pleasure and their poor communication skills are concern for the lecturers.…”
Section: Situational Analysismentioning
confidence: 99%
“…They are observed to be on social media during their leisure time rather than engaging in reading for pleasure. Most of the students lack good communication skills and Choeda et al (2020) found that poor reading habits are a barrier to good communication skills. These behaviors of students towards reading for pleasure and their poor communication skills are concern for the lecturers.…”
Section: Situational Analysismentioning
confidence: 99%
“…The words spoken are often unintelligible making it difficult for listeners to comprehend without any further explanation. Also, in an interview conducted by Choeda et al (2020) for English teachers on communicative proficiency of Bhutanese learners', it was revealed that Bhutanese learners have problems with variation of tone and sound monotonous which makes the discourse difficult to be understood. In the same interview, the struggle of learners in employing stress is recorded.…”
Section: List Of Tables Pagementioning
confidence: 99%
“…Additionally, Singay (2018) reveals that among four modes, Listening & Speaking appears to be deserted skills in the language where pronunciation instruction is embedded. Choeda et al (2020) reviewed that learners are not offered sufficient opportunities to practice authentic language, thus least developing pronunciation. In other words, the exposure and practice are minimal.…”
Section: List Of Tables Pagementioning
confidence: 99%
See 2 more Smart Citations